A compact coupling controllable elliptical filter based on multilayer LTCC - Meng, Fanyi (2013)
This paper presents a compact elliptical filter based on modified λ/4 resonators with separated electric and magnetic coupling paths. For the proposed second-order filters, transmission zero points are generated at either lower or upper stopband by controlling the relative coupling strength in the two paths of inter-stage resonators. Based on the topology and multilayer LTCC technology, a fourth-order bandpass filters operating at 5.2 GHz with a fractional bandwidth of 10% in 1.7 mm × 3 mm (0.0785λg × 0.1385λg) is designed and verified experimentally.